Cardiac echinococcosis with fatal intracerebral embolism. Issue 1 (January 1991) - Byard, R W; Bourne, A J
Abstract : A previously well 7 year old boy presented with sudden loss of consciousness and fitting. No evidence of trauma or space occupying lesion was identified. Death occurred the next day due to cerebral infarction caused by embolised fragments from a ruptured left ventricular hydatid cyst that was found at necropsy.